2009
DOI: 10.2807/ese.14.26.19254-en
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the influenza A(H1N1)v outbreak in Mexico City, April-May 2009, with control sanitary measures

Abstract: We use a time dependent modification of the Kermack and McKendrick model to study the evolution of the influenza A(H1N1)v epidemic reported in the Mexico City area under the control measures used during April and May 2009. The model illustrates how the sanitary measures postponed the peak of the epidemic and decreased its intensity. It provides quantitative predictions on the effect of relaxing the sanitary measures after a period of control. We show how the sanitary measures reduced the maximal prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…One study in Hong Kong showed that school closure during the 2009 H1N1 pandemic reduced the effective reproductive number by 11.8% [ 32 ]. In Mexico and New Zealand, there also have been reported decreases in R t during school closure [ 33 , 34 ]. Contrastingly, in the 2009 pandemic in USA there was no clear effect of school closure detected on transmission [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study in Hong Kong showed that school closure during the 2009 H1N1 pandemic reduced the effective reproductive number by 11.8% [ 32 ]. In Mexico and New Zealand, there also have been reported decreases in R t during school closure [ 33 , 34 ]. Contrastingly, in the 2009 pandemic in USA there was no clear effect of school closure detected on transmission [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various estimates of the reproductive number have been made for the initial phase of the epidemic in different regions of the world [15,[17][18][19][20][21][22][23][24][25][26]. These estimates range from 0.5 to 3.4 [17,27].…”
Section: Estimating the Effective Reproductive Numbermentioning
confidence: 99%
“…Societal reactions can be grouped into different classes. First, there are changes imposed by authorities through the closure of schools, churches, public offices, and bans on public gatherings [25][26][27][28]. Second, individuals self-initiate behavioral changes due to the concern induced by the disease [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%